2020
DOI: 10.1097/txd.0000000000001077
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Preservation Solution Containing Quercetin and Sucrose for Porcine Kidney Transplantation

Abstract: Background. In organ transplantation, the University of Wisconsin (UW) solution has been the gold standard for organ preservation. Quercetin (Que) has numerous antioxidant and anti-inflammatory activities, and sucrose (Suc) may be effective for cold storage (CS). This study aimed to investigate the in vitro protective effect of Que and Suc on cold injury to the kidney and to determine whether Que + Suc could improve ischemia-reperfusion injury during CS and hypothermic oxygenated perfusion (HOPE) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Recently, Gochi M et al. showed the effects of Que and Scr in CS solution and hypothermic oxygenated perfusion (HOPE) in autologous transplantation models ( 116 ). They found that the addition of Que and Scr in preservation solution ameliorated renal function and reduced oxidative stress, preserving renal parenchyma ( 116 ).…”
Section: Strategies Of Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Gochi M et al. showed the effects of Que and Scr in CS solution and hypothermic oxygenated perfusion (HOPE) in autologous transplantation models ( 116 ). They found that the addition of Que and Scr in preservation solution ameliorated renal function and reduced oxidative stress, preserving renal parenchyma ( 116 ).…”
Section: Strategies Of Interventionmentioning
confidence: 99%
“…showed the effects of Que and Scr in CS solution and hypothermic oxygenated perfusion (HOPE) in autologous transplantation models ( 116 ). They found that the addition of Que and Scr in preservation solution ameliorated renal function and reduced oxidative stress, preserving renal parenchyma ( 116 ). Despite these strong results, this study did not demonstrate that Que could exert beneficial effects in long term-outcome ( 116 ).…”
Section: Strategies Of Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained in the case of quercetin. In animal models, a decrease of oxidative stress after IRI was observed [ 91 , 97 , 98 , 99 ], reflected by lower levels of thiobarbituric acid reactive substances (TBARS) [ 100 ] and MDA [ 101 ] as well as an increased activity of antioxidant enzymes [ 101 ]. Additionally, the inhibition of IRI-induced inflammation [ 91 , 99 ] and apoptosis/ferroptosis [ 99 , 102 ], as well as the induction of autophagy [ 103 ], finally resulting in decreased tissue damage, and improved organ function has been observed [ 97 , 98 , 102 ].…”
Section: Curcumin and Quercetinmentioning
confidence: 99%
“…[183,184] p.o. [185] improved organ function increased graft survival [183,184] anti-inflammatory effects shift towards Treg via activation of PPARγ [183,184] inhibition of macrophage recruitment [185] inhibition of MCP-1/IP-10 [185] improved organ function improved shortening of isograft [202] decreased serum LDH [202] improved liver biomarkers (AST, ALT) [202] anti-inflammatory effects decreased serum TNFα [202] decreased serum IL-1 [202] anti-oxidative stress increased SOD activity [202] increased SOD/LPO [202] Quercetin Kidney rat [91,[98][99][100][101] pig [97] in vitro [102] mouse [103] i.p. [91,[98][99][100][101]103] preservation solution [97] anti-oxidative effects [91,[97][98][99] decrease of TBARS [100] decreased MDA [101] increased level of antioxidant enzymes [101] anti-inflammatory effects [91,99] anti-apoptotic effects [99,102] induction of autophagy [103] Liver rat [98,<...>…”
Section: Livermentioning
confidence: 99%